TNF-α Suppresses Autophagic Flux in Acinar Cells in IgG4-Related Sialadenitis. (November 2019) - Hong, X.; Min, S.N.; Zhang, Y.Y.; Lin, Y.T.; Wang, F.; Huang, Y.; Yu, G.Y.; Wu, L.L.; Yang, H.Y.
IgG4-related sialadenitis (IgG4-RS) is a newly recognized immune-mediated systemic fibroinflammatory disease that affects salivary glands and leads to hyposalivation. Tumor necrosis factor–α (TNF-α) is a critical proinflammatory cytokine involved in several salivary gland disorders, but its role and mechanism regarding acinar cell injury in IgG4-RS are unknown. Here, we found that TNF-α level was significantly increased in serum and submandibular gland (SMG) of patients and that serum TNF-α level was negatively correlated with saliva flow rate. Ultrastructural observations of IgG4-RS SMGs revealed accumulation of large autophagic vacuoles, as well as dense fibrous bundles, decreased secretory granules, widened intercellular spaces, swollen mitochondria, and expanded endoplasmic reticulum. Expression levels of LC3 and p62 were both increased in patients' SMGs. TNF-α treatment led to elevated levels of LC3II and p62 in both SMG-C6 cells and cultured human SMG tissues but did not further increase their levels when combined with bafilomycin A1 treatment. Moreover, transfection of Ad-mCherry-GFP-LC3B in SMG-C6 cells confirmed the suppression of autophagic flux after TNF-α treatment. Immunofluorescence imaging revealed that costaining of LC3 and the lysosomal marker LAMP2 was significantly decreased in patients, TNF-α–treated SMG-C6 cells, and cultured human SMGs, indicating a reduction in autophagosome-lysosome fusion. Furthermore, the ratio of pro/mature cathepsin D was elevated in vivo, ex vivo, and in vitro. TNF-α also appeared to induce abnormal acidification of lysosomes in acinar cells, as assessed by lysosomal pH and LysoTracker DND-26 fluorescence intensity. In addition, TNF-α treatment induced transcription factor EB (TFEB) redistribution in SMG-C6 cells, which was consistent with the changes observed in IgG4-RS patients. TNF-α increased the phosphorylation of extracellular signal–regulated kinase (ERK) 1/2, and inhibition of ERK1/2 by U0126 reversed TNF-α–induced TFEB redistribution, lysosomal dysfunction, and autophagic flux suppression. These findings suggest that TNF-α is a key cytokine related to acinar cell injury in IgG4-RS through ERK1/2-mediated autophagic flux suppression.